2000
DOI: 10.1111/j.1471-6402.2000.tb01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Women's Feminist Identity Development: Studies of Convergent, Discriminant, and Structural Validity

Abstract: Researchers have called for increasing sophistication in the assessment of women's feminist identity development (Enns & Hackett, 1990; Hackett, Enns, & Zetzer, 1992) to understand important psychological processes. This series of studies examined recent efforts to operationalize Downing and Roush's (1985) model of feminist identity development. Specifically, the psychometric properties of two existing measures—the Feminist Identity Development Scale (Bargad & Hyde, 1991) and the Feminist Identity Scale (Ricka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
187
2
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(209 citation statements)
references
References 28 publications
14
187
2
6
Order By: Relevance
“…Fischer et al (2000) reported a 5-factor structure that resembled Downing and Roush's (1985) model and was reported to predict ego identity status, perceptions of sexist events, and involvement in women's organizations. Fischer et al (2000) reported internal consistency estimates that range from .68 to .84 for their first sample and .71 to .86 for their second sample. reported internal consistency estimates that range between .73 to .84 in their study.…”
Section: Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…Fischer et al (2000) reported a 5-factor structure that resembled Downing and Roush's (1985) model and was reported to predict ego identity status, perceptions of sexist events, and involvement in women's organizations. Fischer et al (2000) reported internal consistency estimates that range from .68 to .84 for their first sample and .71 to .86 for their second sample. reported internal consistency estimates that range between .73 to .84 in their study.…”
Section: Methodsmentioning
confidence: 64%
“…The Feminist Identity Composite (FIC; Fischer et al, 2000) was developed to assess feminist identity development as a composite of 33 items from two previous measures of feminist identity [i.e., 20 items from the Feminist Identity Scale (Rickard, 1989) and 13 items from the Feminist Identity Development Scale (Bargad & Hyde, 1991)]. Fischer et al (2000) reported a 5-factor structure that resembled Downing and Roush's (1985) model and was reported to predict ego identity status, perceptions of sexist events, and involvement in women's organizations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to sociodemographics, we measured feminist self-identification [22] and feminist values [23] at intake, using validated 7-point Likert scale instruments. Following interaction with the agent, we assessed overall satisfaction, desire to continue, comfort discussing breastfeeding with the agent, and preference to discuss breastfeeding with a doctor or nurse (rather than the agent), in addition to assessing the degree to which the agent was feminist (as a manipulation check), Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Although the findings were consistent across two samples, future research should replicate our work using different measures to capture relevant constructs. For instance, specific measures of feminist beliefs, such as those developed by Henley and her colleagues (Henley, Spalding, & Kosta, 2000) or Fischer et al (2000), would enable researchers to directly assess nonlabelers' feminist perspectives. Further, our measure of ''core beliefs'' of feminism was limited to three items and focused on liberal feminist beliefs about gender equality.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%